Respuesta :
According to the question, we are to complete a 2-column proof to show that the measure of BC is equal to EF:
Given the following:
- BC = EF
- Let BC = EF = x
AC = AB + BC....................... 1
AC = AB + x ............... 2
From equation 2, AB = AC - x ................. 3
Substitute equation 3 into 1:
AC = AB + BC
AC = AC-x + BC
AC-AC = -c + BC
0 = -x + BC
BC = x
Since AC is greater than AB by a value of x, hence AC > BC
Learn more on two-column proof here: https://brainly.com/question/1788884
Answer:
the answer is
BC = EF
Let BC = EF = x
AC = AB + BC....................... 1
AC = AB + x ............... 2
From equation 2, AB = AC - x ................. 3
Substitute equation 3 into 1:
AC = AB + BC
AC = AC-x + BC
AC-AC = -c + BC
0 = -x + BC
BC = x
Since AC is greater than AB by a value of x, hence AC > BC